2022
DOI: 10.1242/dmm.049147
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish embryo as an in vivo model for screening nanoparticle-formulated lipophilic anti-tuberculosis compounds

Abstract: With the increasing emergence of drug-resistant Mycobacterium tuberculosis strains, new and effective antibiotics against tuberculosis (TB) are urgently needed. However, the high frequency of poorly water-soluble compounds among hits in high-throughput drug screening (HTS) campaigns is a major obstacle in drug discovery. Moreover, in vivo testing using conventional animal TB models such as mice is time-consuming and costly, and represents a major bottleneck in lead compound discovery and development. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…The first studies using the zebrafish embryo model tested various clinically established antibiotics. These studies confirmed the applicability of this model for the in vivo evaluation of antimicrobials ( Table S1 , Supporting Information ) (Adams et al 2011 , Bernut et al 2014 , Habjan et al 2021 , Knudsen Dal et al 2022 ). Subsequently, several different pathogen-specific zebrafish infection models have been established for the evaluation of novel compounds (Table 2 ).…”
Section: Evaluation Of Antibacterial Compounds In Zebrafish Embryo In...supporting
confidence: 72%
See 1 more Smart Citation
“…The first studies using the zebrafish embryo model tested various clinically established antibiotics. These studies confirmed the applicability of this model for the in vivo evaluation of antimicrobials ( Table S1 , Supporting Information ) (Adams et al 2011 , Bernut et al 2014 , Habjan et al 2021 , Knudsen Dal et al 2022 ). Subsequently, several different pathogen-specific zebrafish infection models have been established for the evaluation of novel compounds (Table 2 ).…”
Section: Evaluation Of Antibacterial Compounds In Zebrafish Embryo In...supporting
confidence: 72%
“…Another challenge is a differential quenching of fluorescence by the different tissues. Because of these concerns, fluorescence measurement can be combined with determining both the CFU count and the survival of the embryos and studies have shown that these three measurements strongly correlate (Stoop et al 2011 , Stirling et al 2020 , Knudsen Dal et al 2022 ). As a result, fluorescence is nowadays established as a major readout of infection load (Table 1 ).…”
Section: Follow-up Methods For Tracking Bacterial Infection and Asses...mentioning
confidence: 99%
“…However, in vivo testing using animal TB models is time-consuming, costly, and represents a major bottleneck in drug nanocarrier discovery and development. To avoid using mammals, screening studies on zebrafish embryo were also proposed [ 173 ]. The zebrafish TB model emerged as a quick and sensitive tool for evaluating the in vivo toxicity and efficacy of drug formulations in their early stages of development.…”
Section: Discussionmentioning
confidence: 99%
“… RIF@IONPs-PAA-PEG-MAN group was treated with 200 μL, 5 mg/kg for oral administration Direct exposure to high RIF levels and potential excess iron release from RIF@IONPs-PAA-PEG-MAN diminishes intracellular MTB viability. This nanosystem augments innate immune elimination of intracellular MTB by promoting M1 antimicrobial polarization in infected macrophages, boosting proinflammatory/anti-TB cytokine production like TNF-α [ 250 ] Polymeric Micelles 84–149 MIC90 between 0.016 and 0.5 for five water-insoluble nitronaphthofuran derivatives solubilized in polymeric micelles Zebrafish model: 5 mg/kg Encapsulated compounds increased embryo survival by 66–70 % eight days post-infection with a high dose of 50 mg/kg [ 251 ] LNZ-loaded mannosylated gelatin nanoparticles (MAN-GNPs@LNZ) 197–298 Enhanced LNZ concentration in alveolar macrophages due to mannose receptors Wistar rats, 10 mg/kg of LNZ in 5 % w/v gelatin solution MAN-GNPs@LNZ reduced dose, frequency, adverse effects, and prolonged presence in lungs [ 252 ] Nanopolymeric Coordination Systems (SNPC) ∼500 INH/diclofenac (INHDIC) in SNPC inhibited MTB growth in host cells (RAW 264.7) and showed potential against infection. INHDIC also reduced migration in the A549 lung cancer cell line BALB/c mice, INHDIC in PBS suspension with variable doses (5, 25, 50, 100 mg/kg) SNPC-INHDIC was safe up to 100 mg/kg in BALB/c mice.…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%